Pengembangan Perangkat Pembelajaran Matematika berbasis Genius Learning Strategy dalam Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik Kelas XI SMA - Novia Safitri; Edwin Musdi*; I Made Arnawa (Universitas PGRI Madiun, 2022)
The mathematical communication abilities can be defined as students ability in delivering what the students have known through dialugue or interaction that happened in the classroom, this kind of mathematical communication can be happened between teacher and students, books and students, and among students. To improve student communication abilities, lesson plan and worksheet have been made based on genius learning strategy that can create an effective and fun learning processes, also can facilitate students mathematical communication abilities. The research was conducted in order to develop learning tools that have valid, practical and effective characteristics on mathematical communication abilities of eleventh grade students. This research is the development research using the Plomp model, which consists of three stages, namely the preliminary stage, the prototype-making stage and the assessment stage. The learning tools developed are lesson plan and worksheet with Genius Learning strategy in improving students’ mathematical communication abilities for class XI. The instruments used are validation sheets, observation sheets, questionnaires, interviews, and tests. The results showed that: 1) Learning tools that based on Genius Learning strategy in improving students’ mathematical communication abilities have been valid in terms of content and construct. 2) practical because it is easy to be used and understood. 3) From the results of the mathematical communication abilities test, it shows that learning tools based on Genius Learning strategy in improving students’ Mathematical Communication Abilities have been effective to improve mathematical communication abilities according to the results of final test conducted students.